Teacher Problems In Implementing Online Learning During The Covid-19 Pandemic Period (Case Study In Class V at SDN Karangan II Sub District, Jombang Regency) - Ayu Nofitasari; Ratih Asmarani (IJPSE : Indonesian Journal of Primary Science Education, 2022)
This study discusses the Problems of Teachers in the Implementation of Online Learning (Case Study in Class V at SDN Karangan II, Bareng Dsitrict Jombang Regency). This study uses a descriptive approach. The techniques. Data anaysis in this research is data reduction, data presentation, and conclusion drawing. Checking the validity of the data using triangulation of data sources and triangulation methods. The purpose of this study is to describe the process of implementing online learning (online) ini class V during the COVID-19 Pandemic, teacher problems in implementing online learning in class V, and effort made to overcome teacher problems in implementing online learning in class V SDN Karangan II, Bareng District Jombang Regency. The results of this study conclude that (1) the bold learning process in class V at SDN Karangan II has beeb going well. The teacher carries out the planning process (RPP, Smartphones, books and other media), implementation and evaluation by presenting assigments and checking assigments sent by students by taking photos and then sending them via WhatsApp and recaping them in the assessment book. (2) The problems faced by teachers in imoplementing bold learning in class V at SDN Karangan II lack adequate facilities, teachers who are less competent in utilizing information technology, difficult signals during brave learning, there are some students who do not have smart phones, and student discipline in participating in bold learning. (3) Efforts to deal with problems that arise during bold learnign are completing or completing lacking facilities, increasing teacher competence, guiding members and mentoring students on a small scale.